O transporte escolar das escolas públicas no/do campo em Coronel Vivida - Sudoeste do Paraná - Momo, Maria Angela (2024)
This dissertation is linked to the Society, Knowledge and Education research line of the Stricto Sensu Postgraduate Program in Education, master's level, at the State University of Western Paraná - Unioeste, Francisco Beltrão Campus. It addresses a discussion related to school transportation in/of the countryside, which is ensured by public policy that determines the permanence of students enrolled in rural territoriality, as well as in urban school institutions of public schools the right to use it to consolidate and facilitate this access and permanence of students in school. In view of this, school transportation for rural public schools is an essential policy for making the right to education a reality, as advocated in article 208, item VII of the Federal Constitution/1988, which states that the state has a duty towards education to ensure that students are attended to at all stages of basic education, by means of supplementary programs for school teaching materials, transport, food and health care, guaranteeing them the acquisition of artistic, scientific, philosophical and political knowledge specific to the reality that constitutes rural space, which has long been forgotten and denied to peasants. The research has dialectical historical materialism as its theoretical methodological approach, since it seeks to provide a detailed answer to the central object of the research that guided this study, analyzing the process of making public school transport in the countryside in Coronel Vivida effective, in order to understand the historical construction of Countryside Education, analyze the public policies and legislation of school transport in these schools and understand the public policies of the State of Paraná and the municipalities of Southwest Paraná. It should be noted that the research is of a bibliographical documental nature with a qualitative approach of an exploratory nature and with a theoretical basis in various documentary sources, doctrines, resolutions, opinions, decrees, routes and various pieces of legislation. In order to answer the central research question, the work was divided into three chapters. The first discusses the historical construction of rural education and its public policies. The second chapter looks at public policies and legislation on transport for rural public schools in Brazil, Paraná and the southwest of Paraná. The third and final chapter analyzed the Process of Implementing School Transport for Public Schools in/from the Countryside in Coronel Vivida, emphasizing the characteristics of the municipality, its schools and schools in the countryside, how public school transport is carried out, how georeferencing occurs, how the routes are traced, the resources allocated to transport and the sources from which it comes and, finally, what is the role of the school in the construction of subjects to insert the principles of Countryside Education. It is confirmed that in Coronel Vivida, school transport is not fully implemented as established by current legislation, as it does not follow georeferencing, many students spend many hours on the routes until they reach schools, rural students are taken to urban schools, facts worsened by the closure of rural schools over the last few decades. In view of this situation, it is necessary for new public policies to be created and enforced to guarantee equal education for all.